Optimization of process parameters of edge robotic deburring with force control - Burghardt, Andrzej; Szybicki, Dariusz; Kurc, Krzysztof; Muszyńska, Magdalena (Zielona Góra: Uniwersytet Zielonogórski)
The issues addressed in the paper present a part of the scientific research conducted within the framework of the automation of the aircraft engine part manufacturing processes. The results of the research presented in the article provided information in which tolerances while using a robotic control station with the option of force control we can make edge deburring.
Keywords: edge robotic deburring; force control; robots station; 3D scanning